Faster together : accelerating your team's productivity - Stack, Laura (Berrett-Koehler Publishers, 2018)
This book discusses how the author's FAST model mobilizes teams to be the most effective they can be, while keeping each other's best interests at heart. Teams learn to work together Fairly, accept Accountability, apply Systems Thinking, and maximize available Technology. An interactive assessment that helps evaluate a project team's current speed and rate of acceleration is also provided.